Role of Leukocyte–Platelet-Rich Fibrin in Endoscopic Endonasal Skull Base Surgery Defect Reconstruction - Soldatova, Liuba; Campbell, Raewyn G.; Elkhatib, Ahmad H.; Schmidt, Thomas W.; Pinto, Nelson R.; Pinto, Jaime M.; Prevedello, Daniel M.; Ditzel Filho, Leo F.; Otto, Bradley A.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective Advancements in endoscopic endonasal approaches have increased the extent and complexity of skull base resections, in turn demanding the development of novel techniques for skull base defect reconstruction. The objective of this pilot study was to investigate the effect of leukocyte–platelet-rich fibrin (L-PRF) on the postoperative healing after endoscopic skull base surgery.Methods Between January and May of 2015, 47 patients underwent endoscopic endonasal resection of sellar, parasellar, and suprasellar lesions with the application of L-PRF membranes during the skull base reconstruction at two surgical centers. Early postoperative records were retrospectively reviewed.Results We found that 21 days following the surgery, 17/41 patients (42%) demonstrated improvement in the crusting score as compared with their 7 day postoperative examination. Ten of these patients (23%) showed no crusting. Fourteen (34%) patients had no change in the crusting score. Six patient records were incomplete. A total of 4/47 cases (8.5%) had postoperative cerebrospinal fluid leak requiring surgical repair.Conclusion This study demonstrates the potential utility of L-PRF membranes for skull base defect reconstruction. Future studies will be conducted to better assess the role of L-PRF in endoscopic skull base surgery.
Keywords: leukocyte–platelet-rich fibrin; endoscopic endonasal approach; endoscopic skull base surgery; skull base defect reconstruction